Pengaruh Persepsi Siswa Tentang Gaya Mengajar Guru dan Penggunaan Media Pembelajaran Terhadap Minat Belajar Siswa - Vidora Utami; Armida Armida (Universitas Negeri Padang, 2024)
This research purpose to explore several aspects that influence class XI students' interest in learning at SMA Pertiwi 1 Padang. This study purposes to determine the following main outcomes: 1) how students perceive their teacher's style of instruction; 2) how the use of literacy-learning media affects students' interest in learning; and 3) how perceptions of the teacher's style of instruction and media use learning together affect students' interest in learning. This research used causal associative with quantitative methodology as the approach. The entire research population included 242 class XI students of SMA Pertiwi 1 Padang. 150 respondents made up the sample according to the proportional random sampling technique. With the aid of SPSS version 25 software, multiple linear regression was utilized for data analysis. This research results show several important things: 1) Student perceptions regarding the teacher's teaching style have a positive and significant influence on class XI students' interest in learning at SMA Pertiwi 1 Padang, 2) The use of literacy media of learning also has a positive and significant impact on students' interest in learning, and 3) Taken together, perceptions of students' the teacher's teaching style and the use of learning media have a significant and positive influence on students' interest in learning. Based on these results, the conclusion that the combined factors of student perception of teaching style and use of learning media contributed 38.7% to class XI students' interest in learning at SMA Pertiwi 1 Padang.